Relationship between organisational commitment, locus of control and readiness to change among nurses - Julita, Santi (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
The purpose of the present study was to investigate the relationship between organisational commitment and readiness to change. The role of internal locus of control as the moderator variable on the relationship between organisational commitment and readiness to change was also investigated. 120 nurses in Ampang Puteri Hospital were used for the sample of the study. The descriptive analysis, hierarchical multiple regression analysis as well as t-test and analysis of variance were used to test the hypotheses and exploratory analysis. The results indicated that organisational commitment significantly correlated and predicted readiness to change. In addition to that internal locus of control did not act as a moderator in the relationship between organisational commitment and readiness to change. The comparison study mostly showed that there were no differences among demographic variables. However, only length of service was illustrated differently in affective commitment.